Promising photovoltaic efficiency of a layered silicon oxide crystal Si3O - Kim, Sejoong; Chae, Kisung; Young-Woo, Son (Nanoscale, 2020)
Computational searching and screening of new functional materials exploiting Earth abundant elements can accelerate the development of their energy applications. Based on the state-of-the-art material search algorithm and ab initio calculations, we demonstrate a recently suggested stable silicon oxide with a layered structure (Si3O) as an ideal photovoltaic material. With many-body first-principles approaches, the monolayer and layered bulk of Si3O show direct quasiparticle gaps of 1.85 eV and 1.25 eV, respectively, while an optical gap of about 1.2 eV is nearly independent of the number of layers. Spectroscopic limited maximum efficiency (SLME) is estimated to be 27% for a thickness of 0.5 μm, making it a promising candidate for solar energy applications.